Korea's great Buddhist-Confucian debate : the treatises of Chŏng Tojŏn (Sambong) and Hamho Tŭkt'ong (Kihwa) - Muller, A. Charles, 1953-; Chŏng, To-jŏn, 1342-1398; Chŏng, To-jŏn, 1342-1398; Kihwa, 1376-1433 (Korean classics library. Philosophy and religion., 2015)
This work makes available in English the seminal treatises in Korea's greatest interreligious debate of the fourteenth and fifteenth centuries. 'On Mind, Material Force, and Principle' and 'An Array of Critiques of Buddhism' by Confucian statesman Chŏng Tojŏn and 'Exposition of Orthodoxy' by Sŏn monk Kihwa are presented here with extensive annotation.